รูปแบบการใช้นวัตกรรมในการจัดการเรียนการสอนในยุค Next Normal ของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษา จังหวัดลพบุรี: Model of Innovations Using into the Teaching and Learning in the Next Normal Era of Schools under the Lop Buri Primary Educational Service Area Office - Phuwadon Chulasukhont ภูวดล จุลสุคนธ์; Neti Chaloeywares เนติ เฉลยวาเรศ; Suprapa Wiwatniwong สุประภา วิวัฒนิวงศ์; Chonticha Numna ชลธิชา นำนา (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
This research aims to 1) investigate the innovations used in teaching and learning in the Next Normal Era of schools under the jurisdiction of the Lop Buri Primary Educational Service Area Office and 2) develop a model of innovations used in teaching and learning in the Next Normal Era of schools. Using the Yamane technique for stratified random sampling, 357 school administrators and teachers comprised the sample for this study. With a reliability of 0.91, the research instruments consisted of a questionnaire and a structured interview form. The data was analyzed statistically using percentage, mean, standard deviation, and content analysis. The findings showed that: 1) The innovations incorporated into teaching and learning in the Next Normal Era were rated highly overall. In descending order of their mean values, they were arranged as follows: teaching with innovation, school contextual analysis, and evaluation of innovation use. 2) The innovation model for teaching and learning in the Next Normal Era included 1) the CIPP Model assessment 2) the innovations using into the teaching and learning 3) the key factors in the process 4) the outcome of the process and 5) the PDCA cycle that was feasible, useful, consistent, and appropriate for the context, as confirmed by the focus group discussion participants.